Factors Influencing Students' Adoption of Cognitive Strategies in English-Speaking Learning: A Narrative Inquiry - Azizah Putritama Guntur; Dina Rafidiyah; Hafizhatu Nadia; Noor Aida Aflahah; Miftah Al Farhan (UMBanjarmasin, 2023)
This study employs a narrative inquiry approach to investigate the factors influencing students' adoption of cognitive strategies in English-speaking learning. By engaging with five students from various disciplines as resource persons, the research aims to uncover the motivators behind students' preference for cognitive strategies. Through data collection via observation and interviews, the study reveals that students gravitate towards cognitive strategies due to their inclination to practice and learn English within their social circles, such as friends and relatives. Additionally, the findings highlight the influence of social media platforms like Instagram, TikTok, Youtube, and Twitter, which students utilize to enhance their English-speaking skills. These platforms provide exposure to authentic English content and opportunities for interaction with native or proficient speakers. Considering the personal, social, and technological factors at play, educators and language practitioners can harness the impact of interpersonal connections and digital spaces to create a supportive learning environment that fosters collaborative interactions and maximizes language learning potential. This research contributes valuable insights into the intricate dynamics surrounding students' adoption of cognitive strategies and offers guidance for optimizing English-speaking learning practices.